2015
DOI: 10.1371/journal.pone.0144551
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Fibrinogen Deficiency after Surgical Removal of Intracranial Tumors

Abstract: Higher levels of fibrinogen, a critical element in hemostasis, are associated with increased postoperative survival rates, especially for patients with massive operative blood loss. Fibrinogen deficiency after surgical management of intracranial tumors may result in postoperative intracranial bleeding and severely worsen patient outcomes. However, no previous studies have systematically identified factors associated with postoperative fibrinogen deficiency. In this study, we retrospectively analyzed data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…11 Cerebral vasospasm may be seen after skull base surgeries which needs to be managed with triple-H therapy. 12 It has been also seen that intracranial tumour surgery may result in a post-operative fibrinogen deficiency leading to a poor outcomes and increased need for blood transfusions 13 In present study, we saw that the mean heart rate was higher and the mean blood pressure was lower in the transfused group than in the non-transfused group. Similarly, the patients in transfused group received more crystalloid infusion than those in non-transfused group.…”
Section: Discussionsupporting
confidence: 50%
“…11 Cerebral vasospasm may be seen after skull base surgeries which needs to be managed with triple-H therapy. 12 It has been also seen that intracranial tumour surgery may result in a post-operative fibrinogen deficiency leading to a poor outcomes and increased need for blood transfusions 13 In present study, we saw that the mean heart rate was higher and the mean blood pressure was lower in the transfused group than in the non-transfused group. Similarly, the patients in transfused group received more crystalloid infusion than those in non-transfused group.…”
Section: Discussionsupporting
confidence: 50%
“…During surgical resections of intracranial tumours, Wei et al . 17 noted that BMI was closely linked to preoperative-to-postoperative plasma fibrinogen consumption, and postoperative fibrinogen deficiency was a potential risk for postoperative bleeding. Similarly, Ahmed et al .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Wei et al found that larger doses of hemocoagulase might be associated with postoperative fibrinogen deficiency in patients treated with surgical removal of intracranial tumors, which increased the need for blood transfusion (24). Zhou also reported that 7 cases receiving intravenous hemocoagulase developed hypofibrinogenemia after endoscopic excisions of colon polyps (25).…”
Section: Discussionmentioning
confidence: 99%